Manganese catalyzed C–H functionalization of indoles with alkynes to synthesize bis/trisubstituted indolylalkenes and carbazoles: the acid is the key to control selectivity1. Issue 33 (28th April 2015) - Shi, Lijun; Zhong, Xiang; She, Houde; Lei, Ziqiang; Li, Fuwei
<x xml:space="preserve">Abstract</x> The Mn-catalyzed C–H alkenylations of indole with terminal- and/or internal-alkynes have been developed to selectively yield indolylalkene and carbazole.